2021
DOI: 10.1134/s0006297921020048
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids: Dr. Jekyll and Mr. Hyde of Hippocampal Neuroinflammation

Abstract: Glucocorticoids (GCs) are an important component of adaptive response of an organism to stressogenic stimuli, a typical stress response being accompanied by elevation of GC levels in blood. Anti-inflammatory effects of GCs are widely used in clinical practice, while pro-inflammatory effects of GCs are believed to underlie neurodegeneration. This is particularly critical for the hippocampus, brain region controlling both cognitive function and emotions/affective behavior, and selectively vulnerable to neuroinfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 81 publications
1
23
0
Order By: Relevance
“…Excessively secreted GCs in patients with TLE, especially in those with initially abnormal stress response due to the HPACS dysfunction, interact with the hippocampal GRs, inducing signaling pathways that stimulate neuroinflammation and other processes, such as neurodegeneration and changes in neurogenesis [21,41,60]. Functional and structural damages to the hippocampus, which is selectively vulnerable to extreme factors and responds to them by increasing cytokine secretion [115], form an individual basis for the develop ment of both epilepsy and depressive/anxiety disorders in each particular patient.…”
Section: Changes In Neurogenesismentioning
confidence: 99%
“…Excessively secreted GCs in patients with TLE, especially in those with initially abnormal stress response due to the HPACS dysfunction, interact with the hippocampal GRs, inducing signaling pathways that stimulate neuroinflammation and other processes, such as neurodegeneration and changes in neurogenesis [21,41,60]. Functional and structural damages to the hippocampus, which is selectively vulnerable to extreme factors and responds to them by increasing cytokine secretion [115], form an individual basis for the develop ment of both epilepsy and depressive/anxiety disorders in each particular patient.…”
Section: Changes In Neurogenesismentioning
confidence: 99%
“…Mechanisms of these effects of GCs include suppression of glucose transport, glutamate reuptake by astrocytes, alternation of Ca2+ homeostasis and suppression of neurotrophic factors production [ 51 , 52 ]. GCs exhibit either pro- or anti-inflammatory properties, depending on specific features of the definite situation, including the degree and duration of GCs exposure, factors and characteristics of the injury and spatial/temporal aspects [ 53 ]. It is suggested that in the hippocampus GCs may act as pro-inflammatory agents [ 8 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…GCs exhibit either pro- or anti-inflammatory properties, depending on specific features of the definite situation, including the degree and duration of GCs exposure, factors and characteristics of the injury and spatial/temporal aspects [ 53 ]. It is suggested that in the hippocampus GCs may act as pro-inflammatory agents [ 8 , 53 , 54 ]. Importantly, increased level of GCs before a pro-inflammatory stimulus has an additional pro-inflammatory effect [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, GRs are functionally active at stress-induced high GC levels and therefore orchestrate stress responses of the cells, organs, and the whole body. One of the main and most vulnerable targets of GCs is the brain, where excessive or chronic activation of GRs may be detrimental for neuronal function and survival [ 28 , 29 ].…”
Section: Glucocorticoids and Hypoxia-brain Tolerance And Cross-talk Mechanismsmentioning
confidence: 99%